IDENTIFICATION OF PORCINE CIRCOVIRUS TYPE 2 AND PORCINE PARVOVIRUS IN PORCINE STILLBIRTHS AND MUMMIFIED FETUSES FROM SWINE FARMS IN BRAZIL - Rocha, Danilo Leal (2010)
This study investigated the presence of genome sequences of the porcine circovirus type 2 (PCV2) and porcine parvovirus (PPV) in 147 porcine stillbirths and mummified fetuses. These samples, originated from 39 farms located in eight Brazilian states, were collected between 2006 and 2008. Heart and lung fragments were used for extraction of total DNA and later amplification of correspondent fragments of the virus pathogens through polymerase chain reaction (PCR) technique. Out of 147 samples, 74 (50.3%) were positive for PCV2 while nine samples (6.2%) were positive for PCV2 and PPV. None of the samples were positive just for PPV. Out of 39 investigated farms, 21 (53.8%) had fetuses positive for PCV2 while co-infection with PCV2 and PPV was detected in 3 farms (7.7%). These results indicate that PCV2 could be an important infection agent in cases of porcine stillbirths and mummified fetuses in Brazil and must be included at differential diagnostic list. KEY WORDS: Polymerase chain reaction (PCR), porcine circovirus type 2 (PCV2), porcine parvovirus (PPV), reproductive failure, swine.